The Influence of Career Development, Work Motivation and Discipline on Employee Performance BKAD PROVSU - Reza Ananda Harefa; Yohny Anwar; Muhammad Yalzamul Insan (Journal of Management, Economic, and Accounting, 2026)
This study aims to determine the effect of career development, work motivation, and work discipline on employee performance at the Regional Finance and Asset Agency of North Sumatra Province. This study was a quantitative associative study with a sample size of 95 civil servants using a saturated sampling technique. Data were collected through questionnaires and analyzed using SPSS version 25.0, using validity and reliability tests, classical assumptions, multiple linear regression, hypothesis testing, and the coefficient of determination. The results indicate that career development, work motivation, and work discipline have a positive and significant effect on employee performance, both partially and simultaneously. The simultaneous test (F-test) indicates that all three variables together have a significant effect on employee performance, with an F-value of 310.020 > F-table = 3.03 and a sig. = 0.000 < 0.05. The Adjusted R² value of 0.908 indicates that 90.8% of the variation in employee performance is explained by career development, work motivation, and work discipline, while the remaining 9.2% is influenced by factors outside this study.